The Independent and Cumulative Effects of Sibling and Peer Bullying in Childhood on Depression, Anxiety, Suicidal Ideation, and Self-Harm in Adulthood - Dantchev, Slava; Hickman, Matthew; Heron, Jon; Zammit, Stanley; Wolke, Dieter (Frontiers in Psychiatry, 2019)
Sibling and peer bullying are reported as the most frequent forms of violence experienced across childhood. There is now ample evidence indicating an association between sibling and peer bullying, with those reporting sibling bullying at an increased risk of peer bullying. While there is convincing evidence of a causative association between peer bullying and a range of mental health outcomes, sibling bullying continues to receive far less attention. The aim of this study was to explore whether sibling bullying roles (non-involved, victim, bully-victim, bully) in middle childhood were independently associated with clinical diagnoses of depression and anxiety and reports of suicidal ideation and self-harm in early adulthood. We further tested whether there was a cumulative relationship between involvement in sibling and peer bullying victimization. This study was based on up to 3,881 youth from the Avon Longitudinal Study of Parents and Children, a prospective birth-cohort based in the United Kingdom. Sibling and peer bullying was assessed via self-report when youth were 12 years of age, while depression, anxiety, suicidal ideation and self-harm were assessed via self-administered computerized interviews at 24 years of age. Involvement as a sibling bully-victim was associated with clinical diagnosis of depression (OR=1.70, 95% CI: 1.23-2.36), while sibling victims were at increased odds of both suicidal ideation (OR=1.52; 95% CI, 1.16-1.98) as well as suicidal self-harm (OR=2.20, 95% CI, 1.36-3.58) in early adulthood, even after accounting for concurrent peer bullying and a range of other pre-existing childhood confounders. Sibling and peer bullying were further associated in a homotypic manner. A dose-response relationship of bullying in the home and school across mental health outcomes was found. Youth victimized by both their siblings and peers displayed the highest odds of developing clinical depression, suicidal ideation and self-harm. Children bullied at home and at school had no safe place to escape the bullying and torment. Our findings highlight the need for intervention studies tailored toward reducing sibling bullying, as these may hold large promise for alleviating a range of adverse outcomes, including the prevention of peer bullying, which may be contingent on early bullying experiences in the home environment.